THE EFFECT OF VARIOUS STRESS CONDITIONS ON THE PHOSPHORYLATION OF EF-2 IN RABBIT RETICULOCYTE LYSATES - (:unkn) unknown (MBR PRESS INC, 1994)
The phosphorylation of EF-2 by the effects of different experimental conditions which is catalysed by EF-2 kinase III in rabbit reticulocyte lysate has been studied, The phosphorylation of 94 kDa protein which is co-migrated with EF-2 on a denaturing gel was inhibited in the presence of BEM, and cAMP whereas enhanced in the presence of stress causing agents such as high pO(2) and heat shock as well as GDP.
Keywords: ELONGATION FACTOR-II; PROTEIN KINASE-III; MR 100,000 SUBSTRATE; IDENTIFICATION; INITIATION; HEME